Collecting survey-based social network information in work organizations - Agneessens, Filip; Labianca, Giuseppe (Joe) (Social networks, 2022)
•This is a primer of the four major steps to be considered when collecting survey-based network data within organizations.•Negotiating access discusses organizational entry, top management commitment, and what to offer to organizations in return for participation.•Developing a clear a priori network boundary discusses bounding one’s sample and identifying formal structures that shape networks.•We discuss building appropriate sociometric questions and introduce Social Network Data Collection Lab procedures to maximize response rates.•We discuss how to offer advice to the organization without violating organizational members’ confidentiality and ethical concerns. Collecting social network data among organization members using surveys is challenging and requires a well-considered strategy. Based on extensive past experience with collecting social network information in work organizations with surveys, we identify and discuss four major elements of the data collection process, all linked with and dependent on the specific research question and objective: 1) negotiating access to the organization; 2) identifying the network’s boundary, the relevant formal organizational structures that affect social networks, and the sampling approach; 3) deciding how to approach research subjects and collect network data; and, 4) providing useful and ethically-sensitive feedback to the organization and its members. Decisions on each of these elements and their co-alignment, particularly with respect to the chosen research question, is crucial to a successful study. We offer guidelines and provide examples for each of these elements.